2002
DOI: 10.1111/j.1745-6584.2002.tb02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Recharge of a Rising Water Table in Semiarid Niger from 3H and 14C Modeling

Abstract: A hydrodynamic survey carried out in semiarid southwest Niger revealed an increase in the unconfined ground water reserves of approximately 10% over the last 50 years due to the clearing of native vegetation. Isotopic samplings (3H, 18O, 2H for water and 14C, 13C for the dissolved inorganic carbon) were performed on about 3500 km2 of this silty aquifer to characterize recharge. Stable isotope analyses confirmed the indirect recharge process that had already been shown by hydrodynamic surveys and suggested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 21 publications
2
60
1
2
Order By: Relevance
“…Using isotopic analysis and hydrodynamic modelling of the aquifer on a 4000 km 2 zone including the Wankama catchment, Favreau et al (2002a) estimated regional groundwater recharge to have increased by one order of magnitude over the past 50 years, from a 1-5 mm year 1 initial range to 20-50 mm year 1 now. Our hydrological simulations do show an amplification of pond recharge over the period ( Figure 5) but by a factor less than two.…”
Section: Discussionmentioning
confidence: 98%
“…Using isotopic analysis and hydrodynamic modelling of the aquifer on a 4000 km 2 zone including the Wankama catchment, Favreau et al (2002a) estimated regional groundwater recharge to have increased by one order of magnitude over the past 50 years, from a 1-5 mm year 1 initial range to 20-50 mm year 1 now. Our hydrological simulations do show an amplification of pond recharge over the period ( Figure 5) but by a factor less than two.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, natural leakages occur between the unconfined aquifer and confined aquifers at discrete places east of 3°E (Daddy Gaoh and Dassargues, 1995;Guéro et al, 2003). Recent investigations of the water table revealed that, following the regional land clearing observed for the past 50 yr, groundwater levels have risen by a few metres in most parts of the basin in response to a recharge increase of about one order of magnitude Favreau et al, 2002;Guéro et al, 2003). These spatio-temporal changes often require both hydrodynamic and geochemical data to be identified, and must be taken into account for selecting an adequate data set.…”
Section: Indirect Recharge Processmentioning
confidence: 98%
“…1). Le taux de recharge a été estimé de l'ordre de 5 mm par an, à partir des données isotopiques sur la période 1950-1960(Favreau et al, 2002. Toutefois, la dynamique récente de la nappe suggère que la recharge s'est accélérée ces dernières décennies pour avoisiner les 20 mm par an dans les années 1990.…”
Section: Des Aquifères Aux Ressources Abondantesunclassified
“…Les débits spécifiques des ouvrages peuvent atteindre 15 m 3 /h/ m dans la partie centrale du dallol, tandis qu'au-delà, ils ne dépassent que rarement 3 m 3 /h/m. En considérant un taux de recharge variant entre 5 et 25 mm par an (Favreau et al, 2002), Tableau 1. Description des différents types de systèmes irrigués au Niger.…”
Section: Résultatsunclassified